Neurological involvement, immune response, and biomarkers in Kawasaki disease along with its pathogenesis, therapeutic and diagnostic updates [version 2; peer review: 2 approved] - Omniat Amir; Priyadarshi Prajjwal; Mohammed Mahmoud; Soumya Aleti; Omklthoum Alsir; Rayyan Rafik Sunasra; Karan Gupta; Srikanth Gadam; Pugazhendi Inban; Mustafa Elhag (F1000Research, 2023)
Kawasaki disease is an acute, febrile disease that is not typically fatal if treated and affects infants and children more commonly. More than 80% of the afflicted patients are under the age of four. This disease most commonly affects coronary arteries. In a minority of cases, Aneurysms can burst or produce thrombosis, and they can cause infarction. The distinctive redness in the palms and soles of the feet might result from a delayed-type hypersensitivity reaction to a cross-reactive or recently discovered antigen (s). Autoantibodies against epithelial cells and smooth muscle cells are produced as a result of subsequent macromolecule synthesis and polyclonal white blood cell activation, which intensifies the redness. Kawasaki disease's clinical manifestations range from oral skin disease to the blistering of the mucosa, symptoms involving the hands and the feet, skin disease of the palms and soles, a desquamative rash, and cervical lymphatic tissue enlargement (so it is also referred to as tissue layer lymphatic tissue syndrome). Most untreated patients develop some vessel sequelae, from well-organized coronary inflammation to severe arterial blood vessel dilatation to giant artery aneurysms with rupture or occlusion, infarction, and thrombosis. With human gamma globulin administration, reasonable standards of medical care, and the use of analgesics, the speed of symptomatic progression and inflammatory artery changes are reduced. In this review, we have covered the immunology of Kawasaki disease, its biomarkers, and the neurological manifestations of this multisystem illness. We have also included a discussion on its pathogenesis, diagnosis, and treatment.